Failure behavior of polymer microelectrode arrays encapsulated with conventional ALD and 3D-ALI barriers - Martin Niemiec; Fatih Bayansal; Fatih Bayansal; Tejas Bhosale; Steven Suib; Steven Suib; Necmi Biyikli; Necmi Biyikli; Kyungjin Kim; Kyungjin Kim; Kyungjin Kim (Frontiers in Bioengineering and Biotechnology)
As implantable electronics become thinner, softer, and more flexible, there is an increasing need for encapsulation strategies which enable these next-generation devices to survive for sufficient durations in the implanted environment. Atomic layer deposited (ALD) films of metal oxides have been studied for this purpose but suffer from intrinsic incompatibilities with soft and flexible substrates. Additionally, conventional fabrication processes often leave exposed sidewalls vulnerable to moisture permeation, undermining the effectiveness of the encapsulation. In this work, we report an encapsulation method based on atomic layer infiltration (ALI) which eliminates exposed sidewalls while remaining compatible with active microelectrodes for stimulation and recording. We compare the lifetime of sidewall-encapsulated (i.e., 3D) ALI devices under accelerated aging conditions to unencapsulated and conventional ALD-encapsulated groups. Overall, we find that while the 3D-ALI encapsulation successfully reduces sidewall vulnerabilities and offers qualitative improvements in degradation behavior compared to ALD, it did not significantly extend device lifespan. Taken together, these findings highlight both the promise of the 3D-ALI strategy and the need for further study and optimization.